Understanding How Competence, Workload, and Burnout Affect Performance: A Conceptual Framework (International Journal of Scientific Research and Management (IJSRM), 2024)
This paper presents a conceptual framework that examines the multifaceted relationships between competence, workload, burnout, and overall performance across diverse professional environments. The framework posits that competence, defined as the combination of skills, knowledge, and experience, is a critical determinant of performance. However, this relationship is not linear; it is significantly influenced by workload, which can either enhance or hinder performance depending on its intensity and duration. When workload becomes excessive, it often leads to burnout—a state of physical, emotional, and mental exhaustion—which acts as a mediating factor that undermines performance. This study seeks to clarify the effects of competence and workload on performance and investigate the role of burnout in this dynamic. To achieve a thorough theoretical comprehension, a comprehensive literature review has been carried out, covering books, empirical research, an d conceptual papers on nurse performance, competence, workload, and burnout. The proposed framework aims to enhance the existing literature by elucidating the relationships between competence, workload, burnout, and performance, offering a foundation for developing strategies that address workload management and burnout prevention to sustain high levels of performance. The implications of this framework are broad, providing valuable insights for organizational leaders, human resource professionals, and policymakers aiming to optimize performance and well-being in various professional settings.